Fabrication of Bioengineered Skin by Injection Molding: A Feasibility Study on Automation. (October 2019) - Fox, S.; Polak, J.; Schmid Daners, M.; Meboldt, M.
The use of bioengineered skin has facilitated fundamental and applied research because it enables the investigation of complex interactions between various cell types as well as the extracellular matrix. The predominantly manual fabrication of these living tissues means, however, that their quality, standardization, and production volume are extremely dependent on the technician's experience. Simple laboratory automation could facilitate the use of living tissues by a greater number of research groups. We developed and present here an injection molding technique for the fabrication of bilayered skin equivalents. The tissue was formed automatically by two separate injections into a customized mold to produce the dermal and epidermal skin layers. We demonstrated the biocompatibility of this fabrication process and confirmed the resulting bilayered morphology of the bioengineered skin using histology and immunohistochemistry. Our findings highlight the possibility of fabricating multilayered living tissue by injection molding, suggesting that further investigation into this automation method could result in the rapid and low-cost fabrication of standardized bioengineered skin.